2003
DOI: 10.1007/s00441-003-0752-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the small conductance Ca 2+ -activated K + channel, SK3, in the olfactory ensheathing glial cells of rat brain

Abstract: Olfactory sensory neurons are wrapped by ensheathing glial cells in the olfactory nerve layer (ONL). Neither functional roles nor electrical properties of ensheathing glial cells have been, as yet, fully clarified. Four subunits (SK1-4) of small conductance Ca2+-activated K+ (SK) channels have been cloned. In the present study, immunohistochemical analyses showed that SK3 channels are expressed in ensheathing glial cells in the rat olfactory bulb, in addition to neuronal cells in other regions. Western blottin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…For comparison, we also examined the SNC and found that in agreement with previous studies using the same antibody, SK3 reactivity is strongly localized to the SNC (Tacconi et al, 2001; Fujita et al, 2003). Like the SON, these observations correlate with mRNA distribution (Köhler et al, 1996; Stocker and Pedarzani, 2000; Tacconi et al, 2001) and the apamin‐sensitivity of an mAHP (Seutin et al, 1993; Wolfart et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…For comparison, we also examined the SNC and found that in agreement with previous studies using the same antibody, SK3 reactivity is strongly localized to the SNC (Tacconi et al, 2001; Fujita et al, 2003). Like the SON, these observations correlate with mRNA distribution (Köhler et al, 1996; Stocker and Pedarzani, 2000; Tacconi et al, 2001) and the apamin‐sensitivity of an mAHP (Seutin et al, 1993; Wolfart et al, 2003).…”
Section: Discussionsupporting
confidence: 88%
“…The substantia nigra, pars compacta (SNC) is another region known to contain SK3 mRNA (Köhler et al, 1996; Stocker and Pedarzani, 2000; Tacconi et al, 2001) and an apamin‐blockable mAHP (e.g., Seutin et al, 1993; Ping and Sheperd, 1996; Wolfart et al, 2001). SK3 expression is also prominent in the SNC, as judged by studies employing the same antibody as that used here (Tacconi et al, 2001; Fujita et al, 2003). We thus examined the SNC in order to compare the pattern of SK3 expression with that in the SON.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…SK3 is preferentially expressed in phylogenetically older brain regions (thalamus, basal ganglia, cerebellum, brainstem) [47-50]; for instance, KCNN3 mRNA [47] is relatively high in the caudate putamen and in dopaminergic neurons of the substantia nigra, and SK3 immunoreactivity [49] is present in the caudate putamen. Reports of SK3 expression in non-neuronal cells are very limited; it is expressed in astrocytes in the supraoptic nucleus and in olfactory ensheathing glial cells [51,52], and it contributes to vasodilation in response to endothelium-derived hyperpolarizing factor (EDHF) [53]. Here, we observed widely distributed and punctate SK3 immunostaining in the healthy adult rat striatum (except in white matter tracts), and for the first time, have shown SK3 immunoreactivity in microglia in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemical study was carried out by the method described previously [13]. Briefly, wild-type mice were deeply anesthetized with pentobarbital sodium (50 mg/kg À1 , i.p.)…”
Section: Immunohistochemical Studymentioning
confidence: 99%